The Effect of Implementing the Blended Teaching Approach in ESP Courses on Students' Achievement and Attitudes - Aleb, Salma; Labed, Zohra (International journal of education and development using information and communication technology, 2021)
This paper aimed to empirically test whether implementing the blended teaching approach in ESP courses positively affects students' achievement and their attitudes towards it. To this end, explanatory type and quasi-experimental design research were carried out with two groups of students (N = 60) enrolled in the computer science department at Mostaganem University, Algeria. The sample was divided into two equal groups consisting of 30 participants. One group was part of the experimental group, they received instruction through the blended teaching approach, and another group was part of the control group who taught using the traditional teaching approach. Data collection considered two techniques: a test addressed to both groups to compare their performance within different learning environments. A 10-item questionnaire was administered to the experimental group after the treatment phase to investigate the students' attitudes towards implementing the blended approach. The results indicated statistically significant differences between groups in favour of the treatment group both in achievement and attitudes. The educational experience was satisfactory for the students taught within the blended learning environment, which positively affected their academic outcomes. The perceived satisfaction is positively associated with the marks obtained in the ESP subject. Due to the positive results revealed by this study, implementing computerised teaching in addition to the traditional approach is highly recommended. In order to facilitate teachers' mission, the stakeholders in Algerian higher education should take serious steps in improving teachers' information technology skills through providing specialised training programs for the teachers to implement blended learning efficiently and effectively.